Healthy gums does It matter? amlodipine-induced gingival overgrowth (AIGO): a case report - Mohd Zainal, Abdul Zaki Ar Rasyid; Che' Man, Mohamad; Yatim, Yusnita; Mohd Fudzi, Nur Suzieyati Melissa (Academy of Family Physicians of Malaysia (AFPM), 2025)
Background: Calcium channel blockers are one of the recognizable drug-induced gingival overgrowth despite anticonvulsants and immunosuppressants. We report a case of an elderly man with underlying essential hypertension who developed amlodipine-induced gingival overgrowth (AIGO). Case Presentation: A 70-year-old elderly male who has hypertension and dyslipidemia and on daily tablets of amlodipine 10 mg and simvastatin 10 mg for the past 4 years presented with progressive swelling of upper and right lower gums for 3 months. He had painless and gradual enlargement of the gingiva associated with gum discomfort, causing difficulty in chewing, mal-alignment, and loosening of the teeth of the gums involved. Oral examinations show poor oral hygiene with gingival overgrowth found throughout the maxilla and right mandible, especially over the right buccal region. After ruling out other causes, based on clinical findings amlodipine-induced gingival overgrowth was confirmed for this patient. We substituted an angiotensin-converting enzyme inhibitor for amlodipine, and within a few days, the progress of the disease was halted. Discussion: Generally, AIGO occurs within the first 3 months of starting a dose of amlodipine 10 mg/day. As in our patient, however, the enlargement occurred after 4 years of taking the drug at a dose of 10 mg daily. The time duration of gingival overgrowth varies in our case due to multifactorial causes such as genetic susceptibility and host response to drug-induced gingival fibroblasts, interleukins, and matrix-metalloproteinases. Other than that, poor oral hygiene in this patient plays an important role in gingival overgrowth as well. This was supported by the strong relation between inflammation and AIGO demonstrated by the fact that AIGO can be successfully controlled even under continuous amlodipine administration by meticulous professional and individual oral hygiene. Conclusion: Amlodipine is a commonly prescribed antihypertensive drug in primary care, every healthcare practitioner should be aware of this usually overlooked but potentially harmful side effect of generalized gingival overgrowth. Poor oral hygiene is one of the important risk factors for AIGO that need to be addressed, thus frequent dental check-ups are recommended for every patient who is on this medication in order to prevent this adverse effect.